2017
DOI: 10.1136/bmjopen-2016-012567
|View full text |Cite
|
Sign up to set email alerts
|

Risk of tuberculosis in patients treated with TNF-α antagonists: a systematic review and meta-analysis of randomised controlled trials

Abstract: ObjectivesAn increased risk of tuberculosis (TB) has been reported in patients treated with TNF-α antagonists, an issue that has been highlighted in a WHO black box warning. This review aimed to assess the risk of TB in patients undergoing TNF-α antagonists treatment.MethodsA systematic literature search for randomised controlled trials (RCTs) was performed in MEDLINE, Embase and Cochrane library and studies selected for inclusion according to predefined criteria. ORs with 95% CIs were calculated using the ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
101
2
11

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(117 citation statements)
references
References 53 publications
3
101
2
11
Order By: Relevance
“…13 Cumulative TB incidence was higher among patients using belatacept, a fusion protein containing cytotoxic T-lymphocyte associated protein 4 and the Fc-fragment of IgG1. 10,14 Experimental studies suggest that lymphocyte costimulation is necessary for granuloma formation. 10,14 Experimental studies suggest that lymphocyte costimulation is necessary for granuloma formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Cumulative TB incidence was higher among patients using belatacept, a fusion protein containing cytotoxic T-lymphocyte associated protein 4 and the Fc-fragment of IgG1. 10,14 Experimental studies suggest that lymphocyte costimulation is necessary for granuloma formation. 10,14 Experimental studies suggest that lymphocyte costimulation is necessary for granuloma formation.…”
Section: Discussionmentioning
confidence: 99%
“…2 Several studies focusing on clinical presentation and outcomes report that TB occurs primarily within the first year after KT, as a consequence of latent TB reactivation and/or donor-derived infection. 10 The aim of this study was to determine the influence of ISS on the incidence, timing, clinical presentation, diagnosis, treatment, and outcomes of TB after KT. To our knowledge, no studies have investigated the influence of ISS on TB incidence.…”
Section: Introductionmentioning
confidence: 99%
“…The risk of TB is significantly increased in those individuals on anti-TNF-α treatments 8. Anti-TNF-α therapy impairs the ability to form and maintain granulomas, increasing the risk of granulomatous diseases like TB 9.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a substantially increased risk of TB in rheumatologic conditions managed with TNF‐targeted therapies has been demonstrated by several registries . A systematic meta‐analysis of randomized clinical trials also reported almost 2‐fold elevated risk of TB by anti‐TNF‐α agents . Available findings regarding TB risk led to development of guidelines/consensus reports that recommended implementation of screening and, if necessary, chemoprophylaxis in patients who were candidates for anti‐TNF‐α therapy …”
Section: What Is Known and Objectivementioning
confidence: 99%